THE APPLICATION OF KENDURI SKO LOCAL CULTURE AS LEARNING RESOURCES TO INCREASE HISTORY AWARENESS OF STUDENTS (CLASSROOM ACTION RESEARCH IN CLASS SOCIAL X, PUBLIC HIGH SCHOOL 2 KERINCI) - Salvetri, Salvetri (JURNAL PENDIDIKAN ILMU SOSIAL, 2017)
This study aims to overcome the lack of students’ history awareness through the application of local culture of Kenduri Sko as a learning resource. The research was conducted in class X IS 3 SMA Negeri 2 Kerinci. The method used is Classroom Action Research. The results showed that: (1) teachers have implemented learning in accordance with the design of learning; (2) learning history using local culture of Kenduri Sko as a learning resource has succeeded in increasing the awareness of learners' history that is knowledge and understanding of learners about cultural change, interest in history study, pride of local culture; (3) constraints faced by partner teachers is to measure the attitudes and behaviors of learners.